Systems dynamics or agent-based modelling for immune simulation? - Figueredo, Grazziela P.; Aickelin, Uwe; Siebers, Peer-Olaf (Springer, 2011)
In immune system simulation there are two competing simulation approaches: System Dynamics Simulation (SDS) and Agent-Based Simulation (ABS). In the literature there is little guidance on how to choose the best approach for a specific immune problem. Our overall research aim is to develop a framework that helps researchers with this choice. In this paper we investigate if it is possible to easily convert simulationmodels between approaches. With no explicit guidelines available fromthe literature we develop and test our own set of guidelines for convertingSDS models into ABS models in a non-spacial scenario. We also define guidelines to convert ABS into SDS considering a non-spatial and a spatial scenario. After running some experiments with the developed models we found that in all cases there are significant differences between the results produced by the different simulation methods.